Adsorption of Textile Dyes on to Activated Carbons Synthesized from Solid Waste: Decolourizing Power in Relation to Surface Properties - E.A. El-Sharkawy (Adsorption Science & Technology)
Powdered wood of Eucalyptus rostrata (Myrtaceae family) obtained as a solid waste was carbonized at 873 K in a nitrogen flow. The resulting products were activated with steam (CS), zinc chloride (CZ) and phosphoric acid (CA) to obtain three series of activated carbon. The textural properties, including surface area, mean pore radius and total pore volume, were examined from the low-temperature adsorption of nitrogen at 77 K. FT-IR spectroscopy and the base neutralization capacity were used for the detection of surface groups. The adsorption power of the prepared samples for the decolourization of Remazol Brilliant Blue (RBB) and New Coccine (NC) dyes, present as carcinogenic materials in wastewater, was studied at 296 K and 318 K, respectively. FT-IR spectroscopy and the base neutralization capacities indicated the presence of carboxylic and phenolic groups on the carbon surfaces. The type and amount of activator employed had a considerable influence on the textural characteristics of the samples investigated. An increase in the activator/carbon ratio was also associated with the development of porosity and hence with an increase in the specific surface area. The Dubinin–Radushkevich (DR), Langmuir, Freundlich and Weber–Morris equations were all applied satisfactorily for the calculation of various adsorption parameters, e.g. Y m , a, K F and E ads . In addition, the enthalpy of adsorption was also calculated over the temperature interval 296–318 K. It was found that the structures of the two dyes studied and the types and amounts of activators employed had a considerable influence on the adsorption parameters estimated.